Amputation rate following tibia fractures with associated popliteal artery injuries - Roussot, Mark (Department of Health and Rehabilitation Sciences, 2017)
Objectives: 1. Determine the amputation rate; and 2. identify risk factors in patients with tibia fractures and associated popliteal artery injuries. Intervention: Amputation or limb salvage. Design: Retrospective case-control study. Setting: Level 1 trauma center. Patients: Thirty popliteal artery injuries with ipsilateral tibial fractures. Outcome measures: Primary and delayed amputation rates were determined. Risk factors tested for significance (Fischer's Exact) included: mechanism of injury, signs of threatened viability, compartment syndrome, fracture pattern, surgical sequence, and time delay from injury or presentation to revascularization. Results: The study group consisted of 22 males and 8 females, with a mean age of 31 years. Motor vehicle accidents and gunshot wounds constituted the mechanism in 17 and 11 patients respectively. Twenty-one were polytrauma victims. Intra/extra16 articular metaphyseal fractures (OTA 41 A-C) were recorded in 19 and diaphyseal (OTA 42 A-C) in 7 patients. Primary amputation was performed in 7 and delayed in 10 patients (overall rate 57%). No individual risk factors were predictive of amputation; however, the "miserable triad" of a proximal tibia fracture (OTA 41) with signs of threatened viability, and delay to revascularization ≥ 6 hours from injury or ≥ 2 hours from presentation was predictive of amputation (p = 0,036 and p = 0,018 respectively). Conclusions: We should aim to intervene within 6 hours following injury or 2 hours following presentation to reduce the risk of amputation. This provides a target for trauma teams even with uncertain time of injury. Level of Evidence: III.